Optimalisasi Penatalaksanaan Hipertensi melalui Edukasi Penggunaan Nifedipine pada Pasien Lansia Puskesmas Pajang: Penelitian - Suhesti, Iin; Izzah, Raihana Nurul; Ardianto, Riko Tri; Tyas, Hesty Hayuning (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Hypertension is a significant public health issue, especially among the elderly, with a high risk of cardiovascular complications. The use of nifedipine as an antihypertensive drug is effective in lowering blood pressure; however, patient understanding of medication use and healthy lifestyle remains limited. This community service activity aimed to improve knowledge of elderly patients at Puskesmas Pajang regarding hypertension and nifedipine use through educational counseling. The method involved interactive material delivery, leaflet distribution, and a question-and-answer session attended by 27 elderly Prolanis members. The results showed an increased understanding of nifedipine’s mechanism of action, side effects, and the importance of a healthy lifestyle summarized by the acronym CERDIK. The interactive discussion provided participants the opportunity to clarify various questions related to hypertension management. Although there were technical limitations such as leaflet shortages and limited discussion time, the activity successfully enhanced health literacy among the elderly and supported therapy adherence. This activity is expected to contribute to hypertension control and complication prevention at the primary healthcare level.